Chronic Condition Self-Management Surveillance: What Is and What Should Be Measured? - Ruiz, Sarah; Brady, Teresa J.; Glasgow, Russell E.; Birkel, Richard; Spafford, Michelle (Preventing chronic disease, 2014)
The rapid growth in chronic disease prevalence, in particular the prevalence of multiple chronic conditions, poses a significant and increasing burden on the health of Americans. Maximizing the use of proven self-management (SM) strategies is a core goal of the US Department of Health and Human Services. Yet, there is no systematic way to assess how much SM or self-management support (SMS) is occurring in the United States. The purpose of this project was to identify appropriate concepts or measures to incorporate into national SM and SMS surveillance. A multistep process was used to identify candidate concepts, assess existing measures, and select high-priority concepts for further development. A stakeholder survey, an environmental scan, subject matter expert feedback, and a stakeholder priority-setting exercise were all used to select the high-priority concepts for development. The stakeholder survey gathered feedback on 32 candidate concepts; 9 concepts were endorsed by more than 66% of respondents. The environmental scan indicated few existing measures that adequately reflected the candidate concepts, and those that were identified were generally specific to a defined condition and not gathered on a population basis. On the basis of the priority setting exercises and environmental scan, we selected 1 concept from each of 5 levels of behavioral influence for immediate development as an SM or SMS indicator. The absence of any available measures to assess SM or SMS across the population highlights the need to develop chronic condition SM surveillance that uses national surveys and other data sources to measure national progress in SM and SMS.